Mitigasi Bencana Kebakaran Lahan Gambut Di Provinsi Riau Menggunakan Teknologi Modifikasi Cuaca (Studi Kasus: Kabupaten Indragiri Hilir, Kabupaten Kepulauan Meranti, Kabupaten Pelalawan Dan Kabupaten Siak) - Ilvi Rahmi Amalia; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Peat Land in Riau Province have become a routine disaster in recent years. Peat Land occur of because the condition of the peatlands is very deep and triggered by irresponsible parties who tend to clear land by burning. Currently Weather Modification Technology (TMC) is one of the technical solutions that can be used to overcome land fire disasters, by planting NaCl salt in clouds that have the potential to rain. the cloud that is the target of the seeding is the Cumullus (Cu) type cloud. In this study four areas were taken in Riau Province, namely Indragiri Hilir Regency, Meranti Islands, Pelalawan Regency and Siak Regency. With the data used is rainfall data from TRMM satellites and hotspot distribution data from www.fire.globalforestwatch.com. The data obtained were analyzed using FileZilla, GrADS and Command Promt software. From the data analysis, the results of TMC evaluation in general with the mission of increasing rainfall in the four target seeding areas in 2014 and 2016 succeeded in increasing rainfall thus reducing the number of hotspots. So this method can be used to overcome the disaster of land fires in Riau Province.Keywords: TMC, TRMM, Hotspot